Comparison of Haemodynamic Effects of Levobupivacaine and Bupivacaine in Sub-arachnoid Block for Total Abdominal Hysterectomy (Medicine Today, 2020)
Introduction: Altered haemodynamics and arterial hypotension are the most prevalent untoward effects of sub-arachnoid block with bupivacaine. Use of levobupivacaine as pure S (-) - enantiomer of bupivacaine has progressively increased due to its lower cardiotoxicity, neurotoxicity and shorter duration of motor block. This study aimed to compare the haemodynamic status of levobupivacaine and bupivacaine when used with fentanyl in Sub-arachnoid block (SAB) among patients undergone total abdominal hysterectomy.Materials and Methods: This randomized clinical trial enrolled 80 gynaecological patients scheduled for total abdominal hysterectomy under SAB. Forty patients were randomly assigned as trial group (levobupivacaine+fentanyl) and forty as control group (bupivacaine+fentanyl). Main outcome measures in both groups considered intraoperative haemodynamic stability (acute hypotension), cardiotoxicity (bradycardia or tachycardia) and time of administration of first dose of postoperative analgesics.Results: Bupivacaine caused comparatively more significant slowing of heart rate at 25 and 35 minutes of operation. Though no significant differences were found in systolic blood pressure between two groups, bupivacaine caused significant reduction of diastolic blood pressure in comparison to levobupivacaine at 6, 9, 45 minutes and at the end of surgery. Mean pressure found significantly lowered at 6 minutes and at the end of surgery following bupivacaine administration. The incidence of acute hypotension was significantly low in trial group and postoperative analgesia was maintained longer duration with levobupivacaine in control group.Conclusion: Levobupivacaine in comparison to bupivacaine showed more effective and satisfactory haemodynamic stability in sub-arachnoid block with less incidence of intraoperative acute hypotension and provides prolonged postoperative analgesic effect.Medicine Today 2020 Vol.32(1): 29-32